2017
DOI: 10.1038/ncomms14029
|View full text |Cite
|
Sign up to set email alerts
|

Robust microscale superlubricity under high contact pressure enabled by graphene-coated microsphere

Abstract: Superlubricity of graphite and graphene has aroused increasing interest in recent years. Yet how to obtain a long-lasting superlubricity between graphene layers, under high applied normal load in ambient atmosphere still remains a challenge but is highly desirable. Here, we report a direct measurement of sliding friction between graphene and graphene, and graphene and hexagonal boron nitride (h-BN) under high contact pressures by employing graphene-coated microsphere (GMS) probe prepared by metal-catalyst-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 268 publications
(155 citation statements)
references
References 37 publications
8
130
0
Order By: Relevance
“…As illustrated in Figure a–d, three domains (SLG, BLG, and Cu) showing different friction responses in each panel can be clearly distinguished. Friction forces of both SLG and BLG domains are much smaller than that of bare copper substrate since an ideal graphene film is atomically smooth and has no dangling bond, resulting in low shear strength . Friction force of SLG is larger than that of BLG, which is consistent with previous literature .…”
Section: Resultssupporting
confidence: 90%
“…As illustrated in Figure a–d, three domains (SLG, BLG, and Cu) showing different friction responses in each panel can be clearly distinguished. Friction forces of both SLG and BLG domains are much smaller than that of bare copper substrate since an ideal graphene film is atomically smooth and has no dangling bond, resulting in low shear strength . Friction force of SLG is larger than that of BLG, which is consistent with previous literature .…”
Section: Resultssupporting
confidence: 90%
“…The superlubricity, a physical regime in which the friction between two sliding surfaces nearly vanishes (or the sliding friction coefficient is in the level of 0.001),2 is one of the most effective approaches to reduce the frictional energy dissipation and meanwhile provide a near‐wearless condition. There are a series of solid lubricants, such as the diamond‐like carbon (DLC) film and 2D or 3D layered materials, including graphene, graphite, boron nitride, and molybdenum disulfide (MoS 2 ), that have been observed to achieve the superlubricity state under certain special conditions 3. For example, Martin et al observed the superlow friction of a MoS 2 coating in the ultrahigh vacuum, where the atomic origin of superlubricity was from the incommensurate contact of MoS 2 basal planes 4.…”
Section: Introductionmentioning
confidence: 99%
“…Within a generalized Prandtl–Tomlinson model, highly reliable description of the physical processes could be given underlying the measured phenomena . Based on the theoretical and experimental realizations, superlubricity of graphene sliding against graphite with real contact area on nanoscale is found to persist under ultrahigh contact pressure (≈1 GPa).…”
Section: Structural Superlubricity In Homogeneous Interfacesmentioning
confidence: 99%
“…Copyright 2008, American Physical Society; 2016 Reproduced with permission . Copyright 2016, AAAS; 2017 Reproduced with permission . Copyright 2017, Macmillan Publishers Ltd; 2018 Reproduced with permission .…”
Section: Introductionmentioning
confidence: 99%